2002
DOI: 10.1152/ajplung.00428.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular K+ channel expression and vasoreactivity in a model of congenital heart disease

Abstract: K+ channels play an important role in mediating pulmonary vasodilation caused by increased oxygen tension, nitric oxide, alkalosis, and shear stress. To test the hypothesis that lung K+ channel gene expression may be altered by chronic increases in pulmonary blood flow, we measured gene and protein expression of calcium-sensitive (K Ca ) and voltage-gated (Kv2.1) K+ channels, and a pH-sensitive K+ channel (TASK), in distal lung from fetal lambs in which an aortopulmonary shunt was placed at 139 days gestation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…44 Furthermore, altered expression of pulmonary potassium channels associated with an accentuated response to hypoxia has been shown in an ovine model. 45 Mutations in receptors of the transforming growth factor-␤ family (bone morphogenetic protein receptor type 2 and activin-like kinase type 1) have been identified as causes of familial PAH. 15,46 In a recent study, 6% of patients with PAH associated with congenital heart disease were found to have bone morphogenetic protein receptor type 2 missense mutations, a frequency that was comparable to that reported in patients with anorexigen-associated PAH (8%) but was considerably lower than that observed in patients with idiopathic or familial PAH (26% and Ϸ50%, respectively).…”
Section: Pathophysiology and Genetic Factorsmentioning
confidence: 99%
“…44 Furthermore, altered expression of pulmonary potassium channels associated with an accentuated response to hypoxia has been shown in an ovine model. 45 Mutations in receptors of the transforming growth factor-␤ family (bone morphogenetic protein receptor type 2 and activin-like kinase type 1) have been identified as causes of familial PAH. 15,46 In a recent study, 6% of patients with PAH associated with congenital heart disease were found to have bone morphogenetic protein receptor type 2 missense mutations, a frequency that was comparable to that reported in patients with anorexigen-associated PAH (8%) but was considerably lower than that observed in patients with idiopathic or familial PAH (26% and Ϸ50%, respectively).…”
Section: Pathophysiology and Genetic Factorsmentioning
confidence: 99%
“…Persistently increased Q p and pulmonary blood pressure results in an incompletely understood endothelial injury (labeled endothelial dysfunction) marked by an insuffi cient expression of nitric oxide and prostacyclin and an excess production of thromboxane and endothelin-1-the former mediating vasodilatory and antihypertrophic effects, and the latter mediating vasoconstrictive and proliferative effects. Mechanisms to explain endothelial injury mediated by increased sheer stress from chronically elevated Q p and pulmonary blood pressure include increased oxidative and nitrosative stress [16][17][18][19][20][21][22], altered expression of pulmonary vascular potassium channels [23], and induction of fi broblast growth factor and transforming growth factor-β 1 [24][25][26][27][28]. The role of mutations in the bone morphogenetic protein receptor type 2 (BMPR2)-an established locus of familial PAH-has not been fully elucidated in CHD-associated PAH; a recent study that identifi ed missense mutations in 6% of patients with PAH in a wide spectrum of CHD (compared with up to 25% and 50% in idiopathic and familial PAH, respectively) could not exclude the association of the BMPR2 mutations with the congenital heart defect itself [29].…”
Section: Mechanisms Of Increased Pvr In Chdmentioning
confidence: 99%
“…3,4 Lastly, alterations in a myriad of biomolecular entities such as transforming growth factor beta, vascular endothelial growth factor, and vascular potassium channels as well as upregulation of collagens have been noted in animal models or children with congenital cardiac disease with increased pulmonary blood flow. [5][6][7][8] Pulmonary hypertension associated with congenital cardiac disease in the neonate may be associated with several pathophysiological situations. Pulmonary hypertension may be caused by right-to-left shunts and pulmonary overcirculation, with increased pulmonary artery pressure (such as ventricular septal defect, patent ductus arteriosus, truncus arteriosus, aortopulmonary window, and common atrioventricular canal).…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%